Efficiency of Domestic Hygienization of Fertirrigated Lettuces with Wastewater from Dairy Cattle Farming - da Cunha Junior, Paulo Cezar; Silva, Maria Toledo de Carvalho; Cabral, Lais Figueira Gebara; Jorge, Marcos Filgueiras; da Silva, Leonardo Duarte Batista; Rodrigues, Rosane da Silva; Ferreira, Elisa Helena da Rocha (Environmental Management and Sustainable Development, 2023)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Lettuce is the most consumed vegetable worldwide, which has a great economic importance. Its growth demands a large volume of water, encouraging the search for alternative water sources, such as fertigation with cattle wastewater. However, as it is a fecal-origin material, this practice can increase the initial microbial load of the vegetable and affect the efficiency of the sanitation process. Thus, the objective of this study was to evaluate the efficiency of domestic sanitation with sodium hypochlorite solution of lettuces obtained with different dosages of fertigation with wastewater from dairy cattle. After the sanitization, samples of all treatments showed lower number of total Coliforms, <em style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Escherichia coli<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;"> and Aerobic Mesophiles. However, lettuces grown with 200% and 300% of the recommended dose of nitrogen showed microbial counts higher than those declared safe for consumption even after sanitization. There was no development of <em style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Salmonella<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;"> spp. Although the productivity of the vegetable has increased with this irrigation technique, the limit of 100% of the recommended dose of nitrogen must be respected, since higher doses caused the persistence of pathogens at unsafe levels for human health even after the sanitation process. However, fertigation proved to be an outstanding alternative for saving water resources and proper disposal of wastewater.